Pengaruh Tarif Premi, Kualitas Pelayanan, Daya Tarik Iklan, dan Citra Merek Terhadap Loyalitas Nasabah - Paramananda, N.; Satria Pramudana, Komang Agus (E-Jurnal Manajemen, 2015)
This research’s purposed is to examine the effect of premium rates, quality of service, the attractiveness of advertising and brand image on customer loyalty at PT. Prudential Life Assurance. The number of samples taken were 144 respondents. Sampling technique used were purposive sampling method. Data were collected through questionnaires. The analysis technique used is multiple linear regression. The results of this research shows that the premium rates, quality of service, the attractiveness of advertising, and brand image and significant positive effect on customer loyalty at PT. Prudential Life Assurance
Keywords: Key words: premium rates, quality of service, the attractiveness of advertising, brand image, customer loyalty